Bis(trimethylsilyl)phenyl-bridged D-A molecules: Synthesis, spectroscopic properties and for achieving deep-blue emitting materials. (March 2020) - Shen, Ziqiu; Zhu, Xiangyu; Tang, Weiguo; Zheng, Yu; Zhou, Zhikuan; Feng, Xin Jiang; Zhao, Zujin; Lu, Hua
Abstract: Usually, donor (D)-acceptor (A) π -conjugated molecules display weak fluorescence with a long wavelength due to effective intramolecular charge transfer. In this paper, a series of donor- π -acceptor (D- π -A) molecules, incorporated with bis(trimethylsilyl)phenyl as a bridging group to twist molecular structure, were synthesized by Suzuki cross-coupling using diphenylamino and oxadiazole/triazole as electron-donating group and electron-withdrawing group, respectively. The resulting molecules exhibited high thermal stabilities and strong fluorescence at deep-blue regions in the solid state. Aggregation-induced emission enhancement (AIEE) of p -DSiTO was observed because of the suppression of molecular vibration and rotation in the aggregated state. Furthermore, the locally excited (LE) emission was significantly increased to show hybridized local and charge-transfer (HLCT) emission in the aggregated state. Theoretical calculations and electrochemical measurements were carried out for understanding optical and electrochemical properties in these molecules. Non-doped organic light-emitting diodes (OLEDs) fabricated using p -DSiTO as emitter showed deep-blue emission with CIEx, y (Commission Internationale de l'Eclairage) of (0.160, 0.105). Graphical abstract: Image 1 Highlights: D- π -A molecules with bis(trimethylsilyl)phenyl bridge were synthesized. The resulting molecules exhibited strong deep-blue emission. TD-DFT calculations and electrochemical measurements were carried out. Non-doped organic light-emitting diode was fabricated using p -DSiTO as an emitter.